Heart and heart–lung transplantation for idiopathic restrictive cardiomyopathy in children. Issue 1 (19th December 2005) - Fenton, M J; Chubb, H; McMahon, A M; Rees, P; Elliott, M J; Burch, M
Abstract : Objective: To review the outcome of cardiac transplantation for restrictive cardiomyopathy (RCM) in children and to assess the ability of new strategies to modulate the effects of high pulmonary vascular resistance. Design: Retrospective case note analysis of all patients receiving a transplant for RCM. Patients: 18 children with RCM referred for transplantation assessment to Great Ormond Street Hospital, London. Results: Eight boys and 10 girls were referred for assessment. Median age at presentation was 5.0 (mean (SD) 6.1 (4.0)) years. Fourteen orthotopic and two heterotopic transplantations were performed and two patients were referred for heart–lung transplantation. Mean duration from diagnosis to transplantation was 3.3 (3.0) years. Three patients with haemodynamic decompensation before transplantation had increased morbidity in the postoperative period. No patients died while awaiting a transplant. Three patients died in the first year after transplantation, one within 30 days. Five patients received pre-transplantation prostacyclin for a mean duration of 57 (18) days. Transpulmonary gradient was reduced in four of the patients. Mean transpulmonary gradient was 27 (9.8) mm Hg before and 17 (6.7) mm Hg after treatment with prostacyclin (p < 0.05). Conclusion: Most children with RCM require transplantation within four years of diagnosis. Referral for transplantation assessment should precede haemodynamic decompensation. Increase of pulmonary vascular resistance is a variable problem but can be modulated with pre-transplantation prostacyclin. With these strategies, orthotopic transplantation is possible in the majority of cases.